Design for all : ciberarte em exposições interativas - Baptista, Luara Conrado Leite (2017)
The design for all has been approached in debates concerning the new processes of cultural production and establishing itself as an important agenda about interdisciplinarity, collective intelligences, experiences and intersections in the relation spectator-work and in the process of creative. This work aims to discuss the idea that design for all and cyberart can contribute to produce intersections and experiences between different creative processes to generate meaning for all through new formats of cultural mediation from performances / installations, content and digital media, such as immersive environments, digital interfaces, sensors, among other resources capable of providing multisensorial experiences for all.